O jovem Machado de Assis e a tradição retórico-poética nos primeiros poemas - Rodrigues, Cristiane Nascimento (2023)
The present thesis, "The young Machado de Assis and the rhetorical-poetic tradition in the first poems," offers analyses and interpretations of ten poems authored by the literary figure hailing from Rio de Janeiro, originally disseminated through the 19th-century periodical press. Since the colonial era in Brazil, knowledge of Rhetoric and Poetics, along with the practices of Eloquence and Oratory, especially the sacred one, circulated and flourished through manuals, treatises, and compendiums crafted by masters and scholars of the subject. Throughout the 19th century, virtually all Brazilian authors were, in some capacity, steeped in the disciplines of Rhetoric and Poetics, as evidenced by the enduring presence of these subjects in the curriculum of the Colégio Dom Pedro II, a standard educational institution in the country, for almost the entire imperial period. Thus, it is presented here an analytical reading aiming to elucidate how the principles, norms, and rhetorical-poetic values manifest in the composition of Machado's initial poems. To achieve this, a meticulous selection of poetic compositions has been made: “Soneto” à Ilma. Sra. D.P.J.A, “A saudade”, “O pão d’açúcar”, “O meu viver”, “Dormir no campo”, “Minha musa”, “Consummatum est!”, “Cognac!...”, “Álvares de Azevedo” e “Ao Carnaval de 1860”, published, the first, in “Periódico dos Pobres”, by Antônio Maximiano Morando, and, the others, in “Marmotas” by Francisco de Paula Brito.